Hegemony of Power Between Dutch and British Imperialism in Bima in the 18th Century - Subari, Subari; Pertiwi, Yulia Resha (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research is descriptive analysis using historical methods, through several stages of activities which include heuristic, criticism, interperation, and historiography. This research aims to provide an overview of the hegemony and trade war between Dutch and British imperialism in the Bima region. The results of the study show that the factors that encourage the Dutch and British to plant their influence in Bima are generally geopolitical and economic factors. The Dutch-British imperialist rivalry in the region was dominated by the influence of British power while the Dutch gained territorial control over the entire island of Sumbawa. Therefore, hegemony and trade competition have not occurred in open wars between the Dutch and the British in the struggle for power in the area since the XVIII century.